The lived experience of bedwetting in Western Australian male youth - Wilson, Glenice Joyce (Curtin University, 2012)
This phenomenological study describes the lived experience of young men who have persistent bedwetting and live in the Western Australian community. The objectives of the research were to explore and describe these experiences and to set them within the context of existing literature. A purposive sample of six young men agreed to participate in this study and data were collected using semi-structured interviews.The findings revealed that all of the participants, aged between 19 and 27 years used hiding their problem as the primary means of coping with their bedwetting. This was evidenced during all of the developmental stages of pre-adolescence, adolescence and young adulthood. Within the pre-adolescence years the participants believed that their problem could be fixed and they would then be able to live a normal life.However, as they entered adolescence their bedwetting at night began to impact on all aspects of their lives including their identity and the choices they made regarding their future. As they reached young adulthood, all participants spoke of being socially isolated as a means of coping with their problem. At this stage they also came to the realization that their bedwetting may be present for the rest of their lives.These findings reinforce that all health professionals and the community need to be provided with more information regarding this important and currently hidden health issue occurring in young males. The provision of, and access to, appropriate community resources and health services to ensure early diagnosis and support is needed to optimize the quality of life for this group of people.